2017
DOI: 10.1037/pag0000147
|View full text |Cite
|
Sign up to set email alerts
|

Control beliefs and cognition over a 10-year period: Findings from the ACTIVE trial.

Abstract: We examined two facets of control beliefs and cognition over ten-years within the ACTIVE cognitive training program. Intellectual Self-efficacy decreased (β = −0.32 units/year; SE = 0.03) and Concern about Intellectual Aging increased (β = 0.26 units/year; SE = 0.02) over time, with older age being the only predictor of increases in Concern about Intellectual Aging. Although baseline cognitive performance was related to control beliefs over time, the reverse was not supported. Findings were not altered by part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
0
11
0
1
Order By: Relevance
“…In the context of physical activity, researchers have found that higher levels of self-efficacy were predictive of increases in exercise behavior and maintenance of the exercise regimen [45]. In contrast, in the ACTIVE cognitive training trial, it was higher initial levels of cognitive performance that were related to less decline in cognitive-specific self-efficacy, not the other way around [46]. Nevertheless, when examining cognitive interventions, a sense of control may play a role in its effectiveness [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of physical activity, researchers have found that higher levels of self-efficacy were predictive of increases in exercise behavior and maintenance of the exercise regimen [45]. In contrast, in the ACTIVE cognitive training trial, it was higher initial levels of cognitive performance that were related to less decline in cognitive-specific self-efficacy, not the other way around [46]. Nevertheless, when examining cognitive interventions, a sense of control may play a role in its effectiveness [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…Contribuindo para discussão da dimensão da autoeficácia em idosos, estudos longitudinais como o de Parisi et al (2017) encontraram redução da autoeficácia intelectual e aumento na preocupação sobre o envelhecimento intelectual ao longo de um período de 10 anos, indicando um fator temporal nesses declínios. Apesar disso, consideraram ser possível que as crenças internas sejam relativamente duradouras e um pouco resistentes à mudança.…”
Section: Discussionunclassified
“…Indeed, those with lower control beliefs are less likely to use adaptive strategies for cognitive challenges (Lachman & Andreoletti, 2006). Those who have higher control beliefs improve more on cognitive tests with practice and are less likely to show aging-related declines in cognitive functioning (Caplan & Schooler, 2003 (Parisi, Gross, Marsiske, Willis, & Rebok, 2017;Lachman & Leff, 1989). Thus, there is a need to directly address beliefs in cognitive interventions to increase the benefits.…”
Section: Attitudes and Beliefsmentioning
confidence: 99%